الأعمال التي ثوابها خير من حمر النعم -جمعا ودراسة- - كشيدة, مراد (University of Eloued جامعة الجزائر, 2020)
"تناولت هذه الدراسة موضوع الأعمال التي ثوابها خير من حمر النعم، هادفة إلى جمع الأحاديث النبوية التي ورد فيها ذكر هذه الأعمال -من قولٍ أو فعل -وفضلها الموعود به، وتأكيدا لاهتمام الإسلام بهذه الأعمال المباركة؛ فهو يذكّرنا بفضل الله تعالى ونعمه علينا، للتذكير بها وشكرِها، والمحافظة عليها، وكان ذلك من خلال استقراء الكتب الحديثية، وجمع الأحاديث النبوية الخاصة بموضوع الدراسة، وتصنيفها ثم عنونتها بعناوين واضحة ومعاصرة، ثم دراستها وتحليلها. فكانت هذه الأعمال الواردة في هذه الأحاديث كالتالي: صلاة الوتر، وسنة الفجر، وذكر المولى – عزّ وجلّ -، ثم الدعاء والاحتساب عند المصيبة، بعد ذلك قبول رخصة النبي – صلى الله عليه وسلم -، وامتثال أمره – عليه الصلاة والسلام – في مسألة مسح التراب في الصلاة، ثم بعد ذلك الدعوة إلى الإسلام، ورعاية البنات والإحسان إليهم، وختاماً حلق الرأس في الحج. ثم أنهيت بحثي بخاتمة: ذكرت فيها أهم النتائج المتوصل إليها من خلال هذه الدراسة. ""This study deals with the subject of works whose reward is better than the red of blessings, aiming to collect the hadiths of the Prophet in which these actions were mentioned - in words or deeds - and their preference for what was promised, and confirmation of Islam’s interest in these blessed deeds He reminds us of the grace of God Almighty and His blessings upon us, to remind and thank her, and to preserve them, and that was through extrapolating hadith books, collecting hadiths on the subject of study, classifying them, then addressing them with clear and contemporary titles, then studying and analyzing them. The actions mentioned in these hadiths are as follows: Witr prayer, the Sunnah of Fajr, and the mention of the Lord - may He be glorified and exalted -, then supplication and reckoning at the time of the calamity, after that the acceptance of the blessing of the Prophet - may God bless him and grant him peace - and obeying his command - may blessings and peace be upon him - in the matter of wiping dust in prayer, then after that the call to Islam, caring for girls and kindness to them, and finally shaving the head during Hajj. Then I finished my research with a conclusion: I mentioned the most important results obtained through this study. "
مذكرة ماستر تخصص الحديث وعلومه
Keywords: اعمال - ثواب - خير - حمر - النعم; Business - reward - good - red - blessings